Analisis Kelayakan Usaha dan Nilai Tambah Beras IR 42 Pada Usaha Pinukuik Enggi di Kecamatan Batang Kapas Kabupaten Pesisir Selatan - Ririn Handayani; Dang Sri Chaerani; Herda Gusvita (Jurnal Research Ilmu Pertanian, 2022)
The aims of this research are 1). Analyzing the business feasibility of Pinukuik Enggi in Batang Kapas District, Pesisir Selatan Regency 2). Analyzing the added value of Pinukuik Enggi's business in Batang Kapas District, Pesisir Selatan Regency. The method used in this research is descriptive method. Respondents in this study were business owners Pinukuik Enggi in Batang Kapas District, Pesisir Selatan Regency. Sampling used in this research is purposive sampling. The types of data used are qualitative and quantitative. Data analysis was carried out with feasibility analysis and added value. Based on the results of the study, it was found that: 1.) Pinukuik Enggi business in Batang Kapas District, Pesisir Selatan Regency is feasible, seen from the R/C ratio value of 1,79; BEP price Rp. 8.376,06 and BEP volume 205,99 Kg. 2.) The added value obtained in the Pinukuik Enggi business is an average of Rp. 36.692,30/kg or the value-added ratio of 63,22% with an entrepreneur's profit of 55,82%. From the results of the study it can be suggested: 1). It is hoped that business owners can maintain the quality of the pinukuik taste. 2). Trying to make new innovations for processed pinukuik products or creating new recipes without eliminating the uniqueness of the taste of pinukuik itself which will be sold/marketed later